2019
DOI: 10.1097/dcr.0000000000001503
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Surgery Resident Participation in Screening Colonoscopies: How Does It Impact Quality?

Abstract: BACKGROUND: Performing colonoscopies is an integral component of colorectal surgery residency training. There exists a paucity of literature regarding colonoscopy quality metrics with colorectal trainee involvement. OBJECTIVE: This study aimed to investigate the effect of colorectal surgery resident participation on quality metrics in screening colonoscopy. DESIGN: Screening colonoscopies performed between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The ADR, which is directly correlated with the risk of postcolonoscopy colon cancer, and the PDR were not significantly different when trainees were involved and after adjusting for potential confounders. Similarly, prior studies have not found a negative association between trainee participation and the ADR, with the exception of 2 studies that failed to adjust for confounders, 1 small study consisting of only 309 colonoscopies and 1 study involving an unknown number of gastroenterologists and trainees . No prior studies examined the ssPDR as an outcome, which is of particular relevance given the difficulty in detecting sessile serrated polyps.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ADR, which is directly correlated with the risk of postcolonoscopy colon cancer, and the PDR were not significantly different when trainees were involved and after adjusting for potential confounders. Similarly, prior studies have not found a negative association between trainee participation and the ADR, with the exception of 2 studies that failed to adjust for confounders, 1 small study consisting of only 309 colonoscopies and 1 study involving an unknown number of gastroenterologists and trainees . No prior studies examined the ssPDR as an outcome, which is of particular relevance given the difficulty in detecting sessile serrated polyps.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of association with CIR was congruent with 2 prior studies that also reported no difference in the CIR when trainees were involved. 23,29 To our knowledge, no studies prior to ours examined the association between trainee participation and the perforation rate. Although perforation rates were too low in our study for multivariable regression, the crude analysis failed to reveal a difference in this risk when trainees were involved.…”
Section: Jama Network Open | Gastroenterology and Hepatologymentioning
confidence: 91%
See 3 more Smart Citations